Comparative Analysis of Madzhab Zahiriyah and the Madzahib al-Arba'ah through the Study of the Book al-Ittijahat al-Fiqhiyah 'Inda Ashabil Hadith - Nabilah Qothrul Muna; Jamaludin Acmad Kholik (The Institute of Research and Service Community IPMAFA Pati, 2025)
Madzhab Zahiriyah is more often known for its textualist approach to texts as legal ijtihad and for its rejection of the qiyas and ra’y methods. Most of its legal sources are the Qur'an and hadith, which are clearly evident. Some Madzhab also give their opinions on Madzhab Zahiriyah, and compare it to the 4th Madzhab, the Madzahib al-Arba'ah, regarding its legal istinbat. This study aims to examine the relationship between Madzhab Zahiriyah and the four Madzhabs of fiqh (Mazāhib al-Arba'ah), through the literature study research method with the primary source of the book al-Ittijahat al-Fiqhiyah 'Inda Ashhab al-Hadis fi al-Qarni ats-Tsalits, supported by other literature sources. This study examines the relationship between Madzhab Zahiriyah and the Madzāhib al-Arba'ah of fiqh, specifically regarding differences in ijtihad methodology. Although both are based on the Qur'an and Hadith as primary sources, the Madzhab Zahiriyah of thought takes a fundamentally different approach. Madzhab Zahiriyah of thought strongly rejects the use of qiyās, istihsān, and all forms of ra'y-based ijtihad, which are the primary instruments in the legal istinbāṭ methodology of the other Madzahib al-Arba’ah of thought.